2020
DOI: 10.29309/tpmj/2020.27.07.4280
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of male factor and abnormalities of semen analysis in infertile couple.

Abstract: Infertility is global health issue. Male factor contribute to infertility in more than half of sub fertile couples. Their diagnosis is easy by simple test of husband semen analysis. This study has been designed to know the contribution of male factor and frequency of abnormalities of semen in infertile couple. Objectives: To determine the frequency of male factor in infertile couple and to evaluate the different abnormalities in semen. Study Design: Descriptive study. Setting: Department of Obstetrics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…These studies concluded that the semen volume is one of the most important factors associated with infertility. Numerous other studies have also proven that abnormalities in semen volume can impact fertility 13,14 . Similarly, the abnormal appearance, pH, viscosity and liquefaction time of the semen can indicate certain underlying pathologies which must be treated accordingly 12 , as these might be the only reasons preventing successful fertilization 12,13 .…”
Section: Discussionmentioning
confidence: 96%
“…These studies concluded that the semen volume is one of the most important factors associated with infertility. Numerous other studies have also proven that abnormalities in semen volume can impact fertility 13,14 . Similarly, the abnormal appearance, pH, viscosity and liquefaction time of the semen can indicate certain underlying pathologies which must be treated accordingly 12 , as these might be the only reasons preventing successful fertilization 12,13 .…”
Section: Discussionmentioning
confidence: 96%